Pendampingan SDM Tata Kelola Kawasan Kuliner Kelurahan Ledok, Kecamatan Argomulyo Kota Salatiga - Dyah Palupiningtyas; Krisnawati Setyaningrum N; Renny Aprilliyani (Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to provide assistance and assistance to cassava business actors in Ledok Village, Argomulyo District, Salatiga City. Problems identified include a lack of understanding of digital marketing, a lack of attractiveness in packaging design, and the need for increased product branding. Apart from that, the impact of the COVID-19 pandemic has also caused a decrease in their business turnover. This activity involves training, workshops and individual consultations to increase the understanding and skills of business actors in digital marketing, packaging design development and effective branding design. Apart from that, the creation of social media accounts and e-commerce platforms is also carried out to facilitate online product marketing. The results of this activity include increased understanding and skills of business actors, changes in more attractive packaging designs, more effective use of social media and e-commerce, as well as increased sales turnover. The impact involves empowering the local economy, strengthening the business of cassava entrepreneurs, and becoming an inspiration for other business actors